Next‐generation sequencing and clinical outcomes of patients with lung adenocarcinoma treated with stereotactic body radiotherapy. Issue 19 (13th June 2017) - Cassidy, Richard J.; Zhang, Xinyan; Patel, Pretesh R.; Shelton, Joseph W.; Escott, Chase E.; Sica, Gabriel L.; Rossi, Michael R.; Hill, Charles E.; Steuer, Conor E.; Pillai, Rathi N.; Ramalingam, Suresh S.; Owonikoko, Taofeek K.; et al.
Abstract : BACKGROUND: Genetic aberrations are well characterized in lung adenocarcinomas (LACs) and clinical outcomes have been influenced by targeted therapies in the advanced setting. Stereotactic body radiotherapy (SBRT) is the standard‐of‐care therapy for patients with nonoperable, early‐stage LAC, but to the authors' knowledge, no information is available regarding the impact of genomic changes in these patients. The current study sought to determine the frequency and clinical impact of genetic aberrations in this population. METHODS: Under an Institutional Review Board‐approved protocol, the records of 242 consecutive patients with early‐stage lung cancers were reviewed; inclusion criteria included LAC histology with an adequate tumor sample for the successful use of next‐generation sequencing and fluorescence in situ hybridization testing. Univariate analysis was performed to identify factors associated with clinical outcomes. RESULTS: LAC samples from 98 of the 242 patients were reviewed (40.5%), of whom 45 patients (46.0%) had genetic testing. The following mutations were noted: KRAS in 20.0% of samples, BRAF in 2.2% of samples, SMAD family member 4 (SMAD4) in 4.4% of samples, epidermal growth factor receptor (EGFR) in 15.6% of samples, STK1 in 2.2% of samples, tumor protein 53 (TP53) in 15.6% of samples, and phosphatase and tensin homolog (PTEN) in 2.2% of samples. The following gene rearrangements were observed: anaplastic lymphoma kinase (ALK) in 8.9% of samples, RET in 2.2% of samples, and MET amplification in 17.8% of samples. The median total delivered SBRT dose was 50 grays (range, 48‐60 grays) over a median of 5 fractions (range, 3‐8 fractions). The KRAS mutation was associated with worse local control (odds ratio [OR], 3.64; P <.05). MET amplification was associated with worse regional (OR, 4.64; P <.05) and distant (OR, 3.73; P <.05) disease control. CONCLUSIONS: To the authors' knowledge, the current series is the first to quantify genetic mutations and their association with clinical outcomes in patients with early‐stage LAC treated with SBRT. KRAS mutations were associated with worse local control and MET amplification was associated with worse regional and distant disease control, findings that need to be validated in a prospective setting. Cancer 2017;123:3681–3690. © 2017 American Cancer Society Abstract : To the authors' knowledge, no data exist regarding the prevalence of next‐generation sequencing‐detected mutations in patients with early‐stage lung adenocarcinomas who are treated with stereotactic body radiotherapy. Herein, the authors report that the incidence of mutations and gene amplifications in patients with early‐stage lung adenocarcinomas who are treated with stereotactic body radiotherapy is congruent with the advanced disease setting and that patients with KRAS‐mutated tumors appear to have poorer local control and those with MET‐amplified tumors have poorer regional and distant control.